Image Enhancement using DWT (International Journal of Engineering and Computer Science, 2015)
Image enhancement is the method by which we try to develop an image so that it looks subjectively better. We do not reallyknow how the image should look, but we can tell whether it has been improved or not, by considering, for example, whether more detailcan be seen, or whether unwanted flickering has been removed, or the contrast is better etc. Satellite images are used in manyapplications such as Geosciences lessons, stargazing, and terrestrial info systems. One of the most chief quality aspects in images comesfrom its resolution. Interpolation in image handling is a familiar method to increase the resolution of a digital image. The techniqueresolution enhancement is used as a process that enlarges the given input in the way that the output is sharper. The performance of thetechnique over performs all available state-of-art methods for image resolution improvement. In image Resolution enhancement methoda bicubic interpolation technique have been used.